Fast OMP algorithm for 3D parameters super‐resolution estimation in bistatic MIMO radar. Issue 13 (1st June 2016) - Zhang, Dong; Zhang, Yongshun; Hu, Xiaowei; Zheng, Guimei; Tang, Jun; Feng, Cunqian
Abstract : A fast super‐resolution method for joint Doppler frequency, direction of departure and direction of arrival estimation in bistatic MIMO radar is presented. First, the 3D echo signal model of bistatic MIMO radar with uniform linear transmit and uniform linear receive array is established. Then, the Kronecker compressive sensing (KCS) is introduced to improve the 3D parameters estimation performance. Moreover, a novel fast orthogonal matching pursuit (OMP) algorithm utilising 3D fast Fourier transformation is also presented to reduce the computation burden of KCS. Finally, the effectiveness of the method is validated by the simulation.